Anonimity of library users in the Netherlands and Croatia - Schepmann, Tessie (Array, 2008)
A joint research aimed at investigating the existing library practices regarding protection of personal data, in view of computerization of libraries and its consequences, and awareness of the privacy (anonymity) of the library users was carried out simultaneously in the Netherlands and Croatia in the autumn of 2007. The research was a continuation of an on-going co-operation between the Netherlands Public Library Association and the Department of Information Sciences, University of Zagreb. A questionnaire was developed based on previously conducted interviews with librarians and survey of recent literature on anonymity. It was carried out online via a special link on the website of the Netherlands Public Library Association and sent by e-mail to selected libraries in Croatia. Replies obtained from 65 Dutch and 33 Croatian libraries of all types have been compared and commented in the paper. The research shows that in spite of existing differences in library facilities librarians in both countries have not yet become fully aware of all aspects of privacy issues that new services provided by the new technology have brought about, nor received adequate training or taken appropriate measures. Further research in library practices regarding data protection and measures and steps to be taken by libraries in order to improve the present inadequacies can be envisaged in continuation.